ATMOSPHERIC DUST AND ALGAL DOMINANCE IN THE LATE PALEOZOIC: A HYPOTHESIS - Soreghan G.S.; Soreghan M.J. (My University, 2002)
We present preliminary observations suggesting that variations among eolian dust flux, nutrient levels, and primary productivity may have been causally linked during the late Paleozoic icehouse. Modern oceanographic experiments have documented that iron is a limiting nutrient for ocean primary production, and atmospheric dust flux through the Quaternary has been linked to changes in the "biological pump" of the oceans. Eolian silt is remarkably abundant in upper Paleozoic strata, and the late Paleozoic is notable for the dominance of eutrophic, algal- and cement-rich bioherms and near absence of frame-building corals. Within western equatorial Pangea in particular, algal bioherms and eolian dust deposits display a close temporal and spatial relationship. Upper Paleozoic cyclothems in both the marine and terrestrial realms record high-frequency, glacial-interglacial shifts in dust flux within a world characterized overall by high atmospheric dust loads, and geochemical trends through cyclothems suggest cyclical shifts in marine primary productivity. Carbonate carbon isotopes show a strong positive excursion in the late Paleozoic, long attributed to heightened terrestrial productivity, but possibly reflecting increased marine productivity as well. We suggest that the remarkable spatial and temporal coincidence of volumetrically significant eolian siltstone and algal dominance in the late Paleozoic world reflects causation, that is, nutrient seeding of ecosystems by high atmospheric dust loads in an icehouse world. Such a connection implies probable biogeochemical repercussions in the terrestrial, oceanic, and atmospheric realms.
Keywords: Paleozoic; Paleozoic; Палеозой